Distinctive Cellular and Metabolic Reprogramming in Porcine Lung Mononuclear Phagocytes Infected With Type 1 PRRSV Strains - Crisci, Elisa; Moroldo, Marco; Vu Manh, Thien-Phong; Mohammad, Ammara; Jourdren, Laurent; Urien, Celine; Bouguyon, Edwige; Bordet, Elise; Bevilacqua, Claudia; Bourge, Mickael; Pezant, Jérémy; Pléau, Alexis; et al. (Frontiers in Immunology, 2020)
The Porcine Reproductive and Respiratory Syndrome (PRRS) has an extensive impact on pig production. The causative virus (PRRSV) is divided into two species, PRRSV-1 (European origin) and PRRSV-2 (North American origin). Within PRRSV-1, PRRSV-1.3 strains such as Lena are more pathogenic than PRRSV-1.1 strains such as Flanders 13 (FL13). To date, the molecular interactions of PRRSV with primary lung mononuclear phagocytes (MNP) subtypes, including conventional dendritic cells type 1 (cDC1) and type 2 (cDC2), monocyte-derived DCs (moDC) and pulmonary intravascular macrophages (PIM), have not been thoroughly investigated. Here, we analyzed the transcriptome profiles of in vivo FL13-infected parenchymal MNP subpopulations and of in vitro FL13- and Lena-infected parenchymal MNP. The cell specific expression profiles of in vivo sorted cells correlated with their murine counterparts (AM, cDC1, cDC2, moDC) with the exception of PIM. Both in vivo and in vitro, FL13 infection altered the expression of a low number of host genes while in vitro infection with Lena confirmed the higher ability of this strain to modulate host response. Machine Learning (ML) and Gene Set Enrichment Analysis (GSEA) unraveled additional relevant genes and pathways modulated by FL13 infection that were not identified by conventional analyses. GSEA increased the cellular pathways enriched in FL13 dataset, but ML allowed a more complete comprehension of functional profiles during FL13 in vitro infection. Data indicated that cellular reprogramming differed upon Lena and FL13 infection, and that the latter might keep antiviral and inflammatory macrophages/DC functions silent. Although the slow replication kinetics of FL13 likely contributed to differences in cellular gene expression, the data suggest distinct mechanisms of interaction of the two viruses with the innate immune system during early infection.